A lifestyle intervention among elderly men on active surveillance for non-aggressive prostate cancer: a randomised feasibility study with whole-grain rye and exercise. Issue 1 (December 2017) - Eriksen, Anne; Hansen, Rikke; Borre, Michael; Larsen, Ryan; Jensen, Jeppe; Overgaard, Kristian; Borre, Mette; Kyrø, Cecilie; Landberg, Rikard; Olsen, Anja; Tjønneland, Anne
Abstract Background The prognosis for men with non-aggressive prostate cancer is good, and several studies have investigated the impact of lifestyle changes including physical activity and diet on the prognosis. Despite positive results in animal studies and a few human interventions with whole-grain rye on markers of prostate cancer progression, the feasibility of trials investigating such dietary changes in combination with physical activity remains largely unstudied. The primary aim was to investigate the feasibility of an intervention with high whole-grain rye intake and vigorous physical activity for 6 months in men diagnosed with prostate cancer. Methods In total, 26 men (53–72 years) recently diagnosed with non-aggressive prostate cancer and on active surveillance, were enrolled in 2011–2012 and randomly assigned to an intervention or a control group. The intervention included 170 g/day of whole-grain rye and 3 × 45 minutes/week of vigorous physical activity. The duration of the intervention was 6 months and end of follow-up 12 months after baseline. Clinic visits were scheduled at baseline and 3, 6 and 12 months after baseline. Compliance with the intervention was evaluated by diaries, food frequency questionnaires, biomarkers, and heart rate monitor data. The effect of the intervention was evaluated by linear multiple regression analysis. Results In the intervention group, the mean daily intake of whole-grain rye measured from diaries was 146 g (SD: 19) for the first 3 months and 125 g (SD: 40) for the last 3 months of the intervention. The median level (5th and 95th percentiles) of vigorous physical activity was 91 (17, 193) min/week for the first 3 months and 66 (13, 259) min/week for the last 3 months. No recordings of physical activity were done for the control group. Aerobic fitness (VO2 peak) increased in the intervention group compared to the control group after the intervention. No effects were found on other cardio-metabolic outcomes or prostate cancer progression. Conclusions The lifestyle intervention appeared feasible for 6 months among Danish men and the results are encouraging for conducting full-scale studies, where the impact of whole-grain rye and vigorous physical activity on prostate cancer progression and metabolic parameters can be evaluated. Trial registration ClinicalTrials.gov, NCT01300104 . Registered on 18 February 2011.